Preparation and characterization of semi-refined carrageenan from Kappaphycus alvarezii seaweed bleached by Peracetic Acid. (May 2019) - Uju,; Prasetyaningsih, E; Santoso, J; Kamiya, N; Oshima', T
Abstract: Semi-refined carrageenan (SRC) is one of the products from Kappaphycus alvarezii, which has the potential to be developed in Indonesia. However, unbleached seaweed will produce SRC with light brown colour due to natural seaweed pigments. Peracetic acid (PAA) is a strong oxidizing agent that has the potential to be used as a bleaching agent in the SRC production. This research aimed to study the effects of the PAA as a bleaching agent on the characteristics of SRC from K. alvarezii. Chopped seaweed was heated in 10% KOH at 80°C for 30 minutes. Bleaching was carried out at room temperature for 90 minutes using PAA at a concentration of 0.5%, 1.5%, and 2.5% (w/w) or using 1.5% (w/w) of sodium hypochlorite. Bleaching using PAA produced SRC whiter than without bleaching and bleaching using sodium hypochlorite. SRC brightness increased with increasing concentrations of PAA and while the yield reduced, as well as the viscosity, gel strength, sulfate content and ash content. The best concentration of PAA was 0.5%. At best, PAA concentration bleaching produced white SRC flour with a lightness value of 80.46±0.01; yield of 23.50%; viscosity 99.33 cP, gel strength 307.63 g/cm 2, sulfate 13.29% (w/w), ash 8.33% (w/w) and acid-insoluble ash 1.33% (w/w).